Allelopathic effect of pentaclethra macrophylla benth. leaf extracts on germination and seedling growth of maize and okra (2020)
Pentaclethra macrophylla Benth. is an indigenous leguminous tree of southern Nigeria's agroecosystems, whose seeds are used as spices; however, its allelopathy potential is not understood. Therefore, this study was aimed at investigating P. macrophylla allelopathic effects on germination and seedling growth of maize and okra. Materials and Methods: Allelopathic effects of Aqueous Leaf Extracts (ALE) of P. macrophylla at 0 (control), 10, 20, 40 and 80% concentrations on maize (n = 200) and okra (n = 200) seed germination and seedling growth were assessed in laboratory and screen house nursery. Total germination (%) for both crops was determined at one Week After Sowing (WAS); while Number of Leaves (NL), Plant Height(PH) (cm), Root Length (RL) (cm) and Dry Weight (DW) (g) were evaluated at 8 WAS. Experimental design used in the study was completely randomized design. Data were analyzed using descriptive statistics and ANOVA at a0.05. Results: Above 90.0% germination was recorded for maize in all the ALE concentrations, while for okra ALE-10 gave significantly highest germination (90.0±8.7%) and ALE-80 gave least (42.5±26.3%). Maize and okra seedlings given ALE-40 had highest NL, PH and DW;* while ALE-0 (control) had least values in PH and DW, respectively. Control had highest RL in both crops. The ALE-10 gave least RL in maize and ALE-20 gave least RL in okra. Conclusion: Pentaclethra macrophylla aqueous leaf extract at 10% enhanced germination, while 40% concentration encouraged dry matter accumulation and height in maize and okra seedlings.